2022
DOI: 10.3390/s22249987
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Facilitators, Barriers, and Potential Solutions of Adopting Exoskeletons and Exosuits in Construction Workplaces

Abstract: Exoskeletons and exosuits (collectively termed EXOs) have the potential to reduce the risk of work-related musculoskeletal disorders (WMSDs) by protecting workers from exertion and muscle fatigue due to physically demanding, repetitive, and prolonged work in construction workplaces. However, the use of EXOs in construction is in its infancy, and much of the knowledge required to drive the acceptance, adoption, and application of this technology is still lacking. The objective of this research is to identify th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…The age factor can have a significant impact on human function, which may in turn affect the evaluation of exoskeletons by nurses. Some articles have highlighted that younger individuals may be more receptive to the use of exoskeletons compared to older individuals due to differences in physical abilities and preferences [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The age factor can have a significant impact on human function, which may in turn affect the evaluation of exoskeletons by nurses. Some articles have highlighted that younger individuals may be more receptive to the use of exoskeletons compared to older individuals due to differences in physical abilities and preferences [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Exoskeletons should be designed to integrate seamlessly with existing personal protective equipment (PPE) used by nurses, such as gloves and gowns [ 8 , 56 ]. Compatibility with PPE is crucial to ensure that nurses can continue to perform their tasks safely while wearing exoskeletons.…”
Section: Search Strategymentioning
confidence: 99%
“…Mahmud et al [24] identified the facilitator, barriers, and corresponding solutions to overcome the barriers for adoption of EXOs in construction workplaces through a sequential multistage Delphi study. Eighteen experts from academia, industry, and government participated in a workshop to provide insights regarding facilitators, barriers, and potential solutions from a holistic view with respect to business, technology, organization, policy/regulation, ergonomics/safety, and end users.…”
Section: Potential For Exo Use In Constructionmentioning
confidence: 99%
“…Instead, they try to shift the load from one body part to another (e.g., from the shoulders to the waist), which could lead to wearing discomfort and loss of balance due to changes in the center of gravity [26]. If an EXO does not fit the wearer properly, it may exert pressure on unintended body parts, increasing the risk of MSDs, and can cause muscle atrophy due to continuous support from EXOs, such as back belts [24].…”
Section: Potential For Exo Use In Constructionmentioning
confidence: 99%